Intelligent vehicle pollution monitoring using IoT - Chigurupati, Saranyakumar; Teja Vallamsetti, Ravi; Misra, Yogesh; Karthik, Ragipati (International Journal of Engineering and Technology, 2018)
The major source of air pollution is vehicles. The vehicular pollution is increasing day by day and smoke emission from Automobile is causing pollution and also becoming hazardous to people health. An Arduino based prototype is developed to monitor and send the in- formation about the pollution emitted by a vehicle to competent authority. Simultaneously, if the pollution level is high then the vehicle ignition will automatically off by the system. IoT technology has made it possible to send the information about the pollution level in the form of SMS. Â